A Rare Cause of Severe Lower Gastrointestinal Bleeding in Ulcerative Colitis Patients in Remission: Giant Pseudopolyps - Atay, Ali; Yuksel, Ilhami (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Atay A, Yuksel I. A rare cause of severe lower gastrointestinal bleeding in ulcerative colitis patients in remission: giant pseudopolyps. Turk J Gastroenterol. 2025;36(2):131-132.